A Novel, Circulating Tumor Cell Enrichment Method Reduces ARv7 False Positivity in Patients with Castration-Resistant Prostate Cancer - Takehiko Nakasato (Diagnostics, 2020)
Background: The AR-V7 splice variant is a cause of castration-resistant prostate cancer (CRPC). However, testing for the presence of AR-V7 by real-time polymerase chain reaction (RT-PCR) shows AR-V7 positivity in healthy individuals. We hypothesized that the positivity reflects contamination by hematopoietic cells. We tried a novel circulating tumor cell (CTC) enrichment instrument, using Celsee, to clear hematopoietic cells. Methods: We tested whole blood or Celsee-enriched samples for AR-V7 by RT-PCR, and included samples from 41 CRPC patients undergoing sequential therapy. We evaluated the associations between AR-V7 status and clinical factors. We evaluated factors affecting AR-V7 positivity. Results: AR-V7 positivity was lower in Celsee-enriched than in whole blood specimens. AR-V7 and clinical factors did not predict the therapy effectiveness. We found no significant differences in the effectiveness of enzalutamide/abiraterone (Enz/Abi) upon AR-V7 evaluation. All AR-V7 positive patients had resistance to Enz/Abi. Docetaxel (DTX), cabazitaxel (CBZ), and Radium223 treatment showed no significant difference in the treatment effectiveness, regardless of AR-V7 presence. AR-V7 was more frequently positive than Extent of disease (EOD) 2 in cases with bone metastases. Conclusion: Celsee CTC enrichment suppresses AR-V7 false positivity. All AR-V7 positive patients presented resistance to Enz/Abi. DTX, CBZ, and Radium223 were effective and remain treatment options. AR-V7 positivity should progressively appear in patients with advanced bone metastases.